دراسة المسائل المختلف فيها بين مالك وابن القاسم - زقرير, مريم (University of Eloued جامعة الوادي, 2017)
دراسة المسائل المختلف فيها لها دور كبيــــــــــر في بيان مدى قوة الأدلة ووجه الاستدلال مع بيان الراجح والمرجوح منها. قبل دراسة المسائل المختلف فيها بين الإمام مالكــــــــــ والإمام ابن القاسم، أوردت لهما ترجمة لكل منهما ـ رحمهم الله ــ مبحث يدرس حالة العصر، ومدى تأثرهم به، مع لمحات عن السيــــــــــــــرة الذاتية والعلمية، مع إفراد مبحث ابن القاسم ذكر فيه رتبة اجتهاده وأقوال العلــــــــــــــــــــماء فيه. وتطرق إلى بيان معنى الخلاف وأقسامه وذكر أسبابه كذلك بين الفقهاء المذهب المالكـــــــــــــــــي وبين المذاهب الأخرى، وعندما يتضح السبب تسهل عملية الترجيــــــــــح. ولترجيــــــــــــــح عند الاختلاف هنالك طرق بينها العلماء. مع إدراج نمــــــــــاذج من هدي السلف الصالح والفقهاء عند الاختلاف، وذكر الرد على بعضهم البعض بكل أدب وأخلاق. ودراسة المسائل المختلف فيه كانت خاصة في أبواب العبادات من طهارة وصلاة وصوم وزكاة وحج وأيمان ونذور مع بيان مصطلحات، والتعريف بها وذكر المسألة وأقوالهم فيها وأدلتهم ووجه الاستدلال منها. The study of the different issues has a significant role in determining the strength of the evidence and draw the evidence with a more reasonable and likely statement. Before studying the different issues between Imam Malik and Imam Ibn al-Qasim, I reported to them a translation of each of them, may God have mercy on them, a study of the state of the times, and the extent of their influence on them. He referred to the meaning of the dispute and its divisions and its reasons, as well as among the scholars of the Maliki school and among the other sects, and when it becomes clear why it facilitates the process of weighting. With the inclusion of models of the guidance of the Salaf and the scholars when the difference, and the response to each other with all literature and ethics. The study of the different matters in it was especially in the sections of acts of worship of purity, prayer, fasting, zakat, Hajj, faith and vows, with a statement of terms, and the definition of them, and mentioning the issue and their sayings and evidence and drew evidence from them.
مذكرة ماستر تخصص اصول فقه
Keywords: المسائل ــ الاختلاف الفقهي ــ العبادات ــ دراسة ــ; Questions of Differences